Congenital Portosystemic Shunts in Children: Recognition, Evaluation, and Management - Bernard, O.; Franchi-Abella, S.; Branchereau, S.; Pariente, D.; Gauthier, F.; Jacquemin, E. (Seminars in Liver Disease, 2012)
Congenital portosystemic shunts are present in one in 30,000 children. Among the associated risks of severe complications are neonatal cholestasis, benign and malignant liver tumors, hepatopulmonary syndrome, portopulmonary hypertension, and encephalopathy. They can be detected on prenatal ultrasonograms, during the investigation of a positive galactosemia screening test in neonates or of a complication, or be found fortuitously on an abdominal ultrasound. Small intrahepatic shunts may resolve spontaneously within one year of age, but other shunts such as extrahepatic, persistent ductus venosus or persisting intrahepatic shunts, must be closed in one or two steps, by interventional radiology techniques or surgically. The plasticity of the intrahepatic portal system allows revascularization of the liver after shunt closure, even when no intrahepatic portal structures can be detected on imaging studies. This leaves little or no place for liver transplantation in the management of these children.
Keywords: portosystemic shunts; children; liver tumors; hepatopulmonary syndrome; pulmonary hypertension